The influence of removing home advantage on the Chinese Football Super League - Han, B.; Yang, L.; Pan, P.; García-de-Alcaraz, A.; Yang, C.; Liu, T. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Due to the COVID-19 pandemic, the 2020 season Chinese Super League (CSL) was held in neutral venues, this study aims to analyse the impact of removing home advantage (HA) in CSL.